Amenorrhea-An abnormal cessation of normal menstrual cycle - Khan, Nida Tabassum; Jameel, Namra (Clinical Journal of Obstetrics and Gynecology, 2020)
Amenorrhea is the absence or abnormal cessation of menstrual cycles in a woman of reproductive age. Prolonged cessation of menstrual cycles might results in complications such as infertility, psychosocial developmental delays, Osteoporosis, fractures etc. Better understanding of physiology of menstruation is essential to understand the various causes of primary and secondary amenorrhea. Any disruption or functional abnormality in the hypothalamic-pituitary-ovarian axis can result in abnormal menstruation or amenorrhea. Therefore it is crucial to identify this menstrual distress in women at early age to minimize the risks of reproductive dysfunction in premenstrual and postmenstrual conditions.